Releasing time to deliver care: a mixed methods evaluation of the implementation of enhanced midwifery continuity of carer - Paul Wilson; Jo Dumville; Luke Aaron Munford; Elaine Harkness; Charlotte Hall; Stephanie Gillibrand; Kate Parkyn; Maartje Kletter (BMJ Open)
Objectives The enhanced midwifery continuity of carer (eMCoC) pilot programme provided additional resource (funding) to midwifery teams operating in the 10% most deprived areas in England. The eMCoC programme aims to provide additional support to those at greatest risk of poor maternal health outcomes. We conducted a rapid formative evaluation aiming to explore the implementation of the pilot programme to (1) generate timely insights to inform ongoing service delivery; (2) generate a logical framework of the eMCoC service and; (3) inform the design of a longer-term summative evaluation.Design Rapid evaluation using mixed-methods.Setting We explored implementation of the eMCoC service in 58 funded local midwifery teams across 23 Local Maternity and Neonatal Systems (LMNS). We undertook qualitative data collection in 10 case study sites across England, focusing on the implementation in 17 teams.Participants We purposively sampled 34 service users who received care from enhanced teams, and 38 staff working in enhanced teams. Inclusion criteria for the service user interviews included women who had received care from enhanced teams during our evaluation period and were more than 28 weeks pregnant. Exclusion criteria included women who had not received care from our target teams. We undertook descriptive analysis using the Maternity Services Dataset to compare the characteristics of service users in enhanced teams with service users receiving other midwifery service models.Results Many of the 58 teams funded were unable to implement eMCoC during the evaluation period because of institutional and organisational barriers. The barriers identified here are indicative of the barriers associated with implementing midwifery continuity of carer. Largely, the eMCoC service successfully targeted women living in the most deprived areas and a focus on reaching women living in these areas was valued by enhanced teams. Equally, enhanced teams strived to broaden the targeted characteristics (i.e. more broadly than on the basis of deprivation) to include a wider and more diverse set of social risk factors and vulnerabilities, based on local needs and priorities. Service users reported being well supported by the enhanced teams, including receiving relational and well-being support and personalised one-to-one public health education, information and support. Service users emphasised that enhanced teams went ‘above and beyond in their care’.Conclusions Funding for eMCoC has been well received by both staff and service users. The implementation of the enhanced roles was perceived to have supported delivery of team-based care, facilitating successful release of midwifery capacity and the delivery of additional public health activities. Supporting a team-focused ethos seems an important feature of eMCoC services. This was consistent across sites and from both staff and service user perspectives. There appears to be many routes (i.e. different service delivery types) to delivering enhanced care, and the multiplicity of service delivery types found in this evaluation suggests no tightly prescribed way of meeting eMCoC’s objectives. The flexibility of the initial funding specification guidance from NHS England has been a key driver of local ownership and permitted eMCoC services to be organically built ‘from the ground up’. Our conclusions point to the value of autonomy afforded to local areas to use eMCoC funding as they deem necessary to best suit the needs of their staff and specific service user groups. Attention should be placed on the barriers to implementation and sustainability issues which can be addressed, namely: delays in releasing funding from LMNS and Integrated Care Boards to providers, and protecting maternity support worker and midwifery time to their allocated teams.